Perlindungan Hukum Terhadap Hak-Hak Anak Buah Kapal (ABK) Ditinjau Dari Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan - Adolfina Lily Watratan (Comprehensive Law Journal, 2024)
This study aims to determine the fulfillment of the rights of crew members at PT. Kalwedo Kidabela Maluku Tenggara Barat, and to know the factors that cause the rights of crew members at PT. Kalwedo Kidabela Maluku Tenggara Barat is unfulfilled, as well as knowing the efforts of the crew to demand legal protection of unfilled labor rights. The type of research used is the research type of empirical juridical method. Primary data were obtained from interviews with former crew and chief executive officer of PT. Kalwedo Kidabela Maluku Tenggara Barat as well as observation of sea work agreement. Secondary data is obtained from the literature study of legislation and books on employment. From the results of research at PT. Kalwedo Kidabela Maluku Tenggara Barat, still lacking in fulfilling the rights of crew which only provide wages according to position, dining facilities and bed on board, health, work accident in marine working agreement. Factors that do not fulfill the rights of crew members at PT. Kalwedo Kidabela Maluku Tenggara Barat in terms of work agreement and law. In terms of agreement there are several things including the absence of subsidies from the central government, cheap ticket prices, thin routes (capacity on very few passengers), and rising fuel prices. Legislation lacks understanding of crew on workers 'rights regulated in legislation and lack of budgetary funds to meet workers' rights needs. The efforts of the crew are bipartite efforts to negotiate with the company, but do not respond to it so that negotiations have failed in accordance with Article 3 paragraph (3) of Law no. 2 of 2004 on Industrial Relations Completion and the absence of a treatise so that it can not proceed to the tripartite phase.